2006
DOI: 10.1111/j.1570-7458.2006.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional response ofTrichogramma chilonistoGalleria mellonellaandChilo sacchariphaguseggs

Abstract: A biological control programme using inundative releases of Trichogramma chilonis Ischii (Hymenoptera: Trichogrammatidae) reared on Galleria mellonella L. (Lepidoptera: Pyralidae) is currently underway to reduce infestations of Chilo sacchariphagus Bojer (Lepidoptera: Crambidae) in sugarcane, Saccharum spp., on Réunion Island. To assess the potential of the parasitoid as an inundative biocontrol agent, the functional response of three T. chilonis strains was tested with G. mellonella and one strain with C. sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…texanus Cresson, which is type II (Ulliett 1949, Holling 1959, Hassell 1978. It is necessary to point out that other braconid species also present a type III response (Montoya et al 2000, Rakhshani et al 2004) and this is relatively important in other hymenopteran species as well (Jones et al 2003, Wang et al 2006, Chen et al 2006, Wang and Ferro 1998Reay-Jones et al 2006). With regard to these discrepancies, we have to point out that in various entomophagous species (predators and parasitoids) their functional response can change from type II to type III when they are offered non-natural or inadequate prey or hosts (van Alphen and Jervis 1997).…”
Section: Discussionmentioning
confidence: 94%
“…texanus Cresson, which is type II (Ulliett 1949, Holling 1959, Hassell 1978. It is necessary to point out that other braconid species also present a type III response (Montoya et al 2000, Rakhshani et al 2004) and this is relatively important in other hymenopteran species as well (Jones et al 2003, Wang et al 2006, Chen et al 2006, Wang and Ferro 1998Reay-Jones et al 2006). With regard to these discrepancies, we have to point out that in various entomophagous species (predators and parasitoids) their functional response can change from type II to type III when they are offered non-natural or inadequate prey or hosts (van Alphen and Jervis 1997).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, T. brassicae presents a type-I functional response both at 20 and 30 o C, when it parasitized previously-non-exposed eggs (Figure 1). However, changes in the functional response of Trichogramma have been reported due to the effect of temperature (Wang and Ferro 1998) or the host typology (Reay- Jones et al 2006). On the contrary, functional responses change to type III when females must parasitize previously-parasitized eggs, which is a highly frequent phenomenon under natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with the findings of Jamshidnia et al (2010), who showed a type III functional response for T. busseolae on S. nonagrioides eggs at different temperatures. The type III functional response of Trichogramma chilonis to Galleria mellonella eggs was attributed to superparasitism at low densities of the hosts (Reay-Jones et al, 2006). Although the type of functional response could be affected by factors such as temperature, host plant and host species (Juliano and Williams, 1985;Messina and Hanks, 1998;De Clercq et al, 2000;Mohaghegh et al, 2001), the shape of T. busseolae functional response was not affected by these factors.…”
Section: Discussionmentioning
confidence: 97%